HUKUM SEBAGAI SUATU SISTEM (PERBANDINGAN SISTEM KONSTITUSI DI NEGARA INGGRIS DAN TURKI) - Awaluddin, Awaluddin (AKTUALITA, 2011)
Asystem of law in narrow sense can be defined as the rule or institution of law in acountry. A legal system in real is a complex organism which the structure, substance, andlegal cultures are interact each other.Keywords: Comparison of the system, Law as a system